Development of basic and special endurance in age-group swimmers - Vorontsov, A. R.
In accordance with known patterns of growth and development of motor and psychological abilities, multi-year training (MYT) to the time when excellence should be achieved is subdivided into several stages. Each stage has its own objectives primarily determined by the peculiarity of development and maturity. Four stages of MYT are commonly proposed and are the foundation for planning of training for young swimmers and explained here: 1. THE STAGE OF PRELIMINARY SPORT PREPARATION, 2. THE STAGE OF BASIC TRAINING, 3. THE STAGE OF SPECIALIZATION, 4. THE STAGE OF EXCELLENCE. From these basics article mainly descusses the endurance development in young swimmers: THE DEVELOPMENT OF BASIC ENDURANCE-1, THE DEVELOPMENT OF BASIC ENDURANCE-2, DEVELOPMENT OF ANAEROBIC ENDURANCE, DEVELOPMENT OF ANAEROBIC-ALACTIC ENDURANCE. EXERCISES FREQUENTLY USED FOR DEVELOPING ENDURANCE IN AGE-GROUP SWIMMERS are presented.